Modulating mind-wandering in dysphoria - Murphy, Fionnuala C.; Macpherson, Kirsty; Manly, Tom; Dunn, Barnaby D. (Frontiers in Psychology, 2013)
Depression is associated with significant difficulty staying ‘in the moment’ as the mind tends to wander away from current activity to focus instead on personal concerns. Mind-wandering (MW) may in some instances be a precursor for depressive rumination, a thinking style believed to confer vulnerability to the likelihood and extent of depression. Though the majority of evidence examining MW and mood has been correlational, evidence indicates that MW may be not only a consequence but also a cause of low mood. Identifying a paradigm that could modulate MW, particularly in depressed individuals, would allow future studies to test whether elevated rates of MW causally drive cognitive-affective features of depression, such as rumination and anhedonia. This study therefore explored the feasibility of using an existing task manipulation to modulate behavioural and self-report indices of MW in participants with varying levels of self-reported dysphoria. Participants completed two go/no-go tasks – the SART and a high target probability task – and measures of state and trait MW. The two tasks were identical in all respects apart from the lower probability of no-go targets on the SART, a feature considered to encourage mindless, or inattentive, responding. Across participants, errors of commission (a behavioural indicator of MW) were elevated on the SART relative to the high probability task, a pattern than was particularly pronounced in dysphoric participants. Dysphoric individuals furthermore reported elevated levels of MW, though the modulation of these subjective reports by task was present to a similar rather than greater extent in the dysphoric individuals. These findings provide encouraging preliminary support for the use of this paradigm as one that modulates MW in depressed individuals. The implications of these results and directions for future research are discussed.